Entre o espaço público e o espaço privado - contributo e ambiguidades no desenho urbano - Inês Silva Vieira (2017)
The present dissertation takes as study basis the transformation of the urban space and itsconsecutive interference in the facts that organize it. The discontinuity of the public space,as well as the increased complexity of the relations established between different elementsand domains, has motivated the study of the elementary contributions conferred by privateexternal spaces open to public usufruct, being these directed to the filling of these ruptures- spatial and social -, and to the regeneration of a continuous and articulated strategy- a system.These spaces, usually linked to public or private buildings, demand a look beyond thearchitectonic object and its programmatic requirements, considering the diversity of experiencesand particularities that justify the possible addition of ambiguity. Although the field of interventionis reduced to the architectural scale, concentrating in one place the study of several subjects,there are also repercussions at the urban scale, since one of the main purposes of these spaces isbased precisely on the resolution or refine of the surrounding issues. Thus, in order to counteractthe fragmentation of the urban space, while recognizing, at the same time, the autonomyof each stratum and its unique contribution to the prosperous, balanced and congruentfunctioning of the system, it will be scrutinized in what measure the social and community natureof the spaces in question - common to the public and private by the transition that materialize- could enable a lively, inclusive and evolutionary urban landscape. Considering also that thebest way to preserve a space - or, in this case, a network of (public) places - is through its use,the coherent strategy will be to promote a flexible and adaptable use to the metamorphosis thatextends in time and space.The construction of an idea brings together, through research and participatory dialogue,opposing notions, being the presente dissertation the result of the conciliation betweenconcepts, understandings and personal ideas, giving rise to the production of principlesapplicable to the critical study of future project processes.